Investigating of Lecturers and Learners Foreign Language Anxiety in E- Learning Interaction - Sadapotto, Andi; Hermansyah, Sam; Juniarti, Juniarti; Lince, Lince; Risnah, Risnah (La Ogi : English Language Journal, 2022)
The objectives of the research are to know the anxiety of the lecturers and the learners foreign language anxiety in E- learning interaction , The subjects of this study were students of muhammadiyah Sidenreng Rappang University consisting 21 students as a sample from fourth semester of English departement and 5 English lecturers of muhammadiyah Sidenreng Rappang University. The qualitative research method was used in this study. Questionnaires and interviews were used to collect data. Based on the results of the questionnaire and interviews with subjects, the factors of students' anxiety in speaking English are classified into three major types of anxiety, namely test anxiety, communicative apprehension, and fear of negative evaluation. Keywords :Foreign language learner, lecturer ,anxiety, E-Learning